Theory of Faults (ToF): Numerical Quality Management in Complex Systems - Niv Yonat; Igal M. Shohet (Applied Sciences)
The purpose of this manuscript is to provide general system theory concepts and practical tools for management under complexity. Built environments and infrastructure are produced, operated, and maintained by information systems; they are also integral components of information systems themselves. These systems are self-organized and teleonomic. The complexity inherent in built environments and infrastructure systems poses a challenge to research, hindering forecasting and the implementation of managerial tools. The use of faults, which are complex systems’ responses to penetrating risk, provide us with databases of and windows into complex systems. This manuscript presents an explicatory theory (ToF), develops it mathematically, expands it through numerical experiments, validates it by case studies, and relates it to practice by expert contributions. A statistical analysis provides a phase parameter, descriptive statistics elucidate trending and emergent behaviors, digital signal processing expounds the effects of signals on information overload, and a directed-network analysis portray morphology, entropy, and time effects. The novelty of ToF is in the application of complexity theory to construction to produce data analysis tools and a managerial framework.